2016
DOI: 10.1002/jor.23231
|View full text |Cite
|
Sign up to set email alerts
|

Utility of an allograft tendon for scoliosis correction via the costo‐transverse foreman

Abstract: Current convex tethering techniques for treatment of scoliosis have centered on anterior convex staples or polypropylene tethers. We hypothesized that an allograft tendon tether inserted via the costo-transverse foramen would correct an established spinal deformity. In the pilot study, six 8-week-old pigs underwent allograft tendon tethering via the costo-transverse foreman or sham to test the strength of the transplanted tendon to retard spine growth. After 4 months, spinal deformity in three planes was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Tethering procedures have received increasing interest for fusionless treatment of adolescent idiopathic scoliosis. A posterior allograft tendon tether was effective at controlling spinal deformities in growing pigs, suggesting this method shows promise as a potential method for scoliosis correction …”
Section: Surgical Repair Scoliosis and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tethering procedures have received increasing interest for fusionless treatment of adolescent idiopathic scoliosis. A posterior allograft tendon tether was effective at controlling spinal deformities in growing pigs, suggesting this method shows promise as a potential method for scoliosis correction …”
Section: Surgical Repair Scoliosis and Infectionmentioning
confidence: 99%
“…A posterior allograft tendon tether was effective at controlling spinal deformities in growing pigs, suggesting this method shows promise as a potential method for scoliosis correction. 24 Although relatively uncommon, post-operative spinal infections can be a devastating complication after spinal surgery, and a mouse model of spine implant infection was developed using in vivo bioluminescence and fluorescence imaging to non-invasively quantify bacterial burden and host inflammation longitudinally. 25 A composite biomaterial strategy used to treat a rabbit in vivo spinal tuberculosis model found that anti-tuberculosis drugs had better penetration using hydroxyapatite microspheres but poly (lactic-co-glycolic acid) carriers were better for distribution.…”
Section: Surgical Repair Scoliosis and Infectionmentioning
confidence: 99%